Ecologies of Architecture : Essays on Territorialisation - Andrej Radman (Edinburgh University Press, 2021)
Drawing on a range of philosophical texts, Andrej Radman brings together a collection of 11 of his essays, published over the last decade, to show that when a society manipulates its matter it is not a reflection of culture; it is culture. To speak of ecologies of architecture is to break with judgement for experience. As Gilles Deleuze put it in his book on Nietzsche, it is not about justification, ‘but a different way of feeling: another sensibility'. If to think differently we have to feel differently, then the design of the built environment has no other purpose but to transform us. While engineering is solution-oriented, architecture stays with the problem so as to tease out a creative potential.